Lateralis-Based Dorsal Cross-Finger Flap - M. Jailani M. Jailani (Universitas Syiah Kuala, 2006)
Abstrak. Hilangnya jaringan lunak pada jari tangan harus di usahakan di tutup dari daerah sekitarnya, Lateral- based dorsal cross-finger flap yang dan dapat digunakan untuk berbagai keadaan. Kulit jari tangan pada bagian lateral mempunyai vaskularisasi yang berjalan longitudinal sehingga dapat digunakan sebagai flap dengan aman. Keadaan ini dijadikan aliran balik yang sangat baik sehingga dapat digunakan sebagai flap. Dilaporkan sebuah kasus, pasien laki-laki 29 rahun, pasca crush injury dari jari V tangan kiri. Terdapat defect kulit beserta soft tissue ditutup dcngan lateral-based dorsal cross-finger flap dari jari IV. (JKS 2006; 2:8 7-90) Kata Kuuci : Lateral based , dorsal cross finger flap. Abstract. The repair of major soft-tissue losses of the digits should be accomplished with local tissues whenever practical.The cross finger flap is a sturdy, versatile flap that can be use in any situations. Dorsal finger skin is basicallyvascularized by a network of longitudinally crieted vrssels that permit wide latitude of flap design with safety. This provides excellent retrograde flow, permitting long flaps to be based distally. Reported one case, a 29 years old, male patient with post crush injury or the finger V. there was skin defect in the dorsal finger IV that has been treated by laterally-based dorsal-finger flap. (JKS 2006; 2:87-90) Keyword: Lateral Based, dorsal cross finger flap.